The Effectiveness of Lemon Aromatherapy in Reducing Pregnant Women's Anxiety Before Childbirth - Eriyani, Novi Rida; Contesa, Lina; Handayani, Tri Restu; Yunus, Mohd (Yayasan Ahmad Mansyur Nasirah, 2025)
Anxiety approaching labour is a common phenomenon experienced by many pregnant women, particularly those giving birth for the first time. A high level of anxiety can negatively affect the labour process, leading to less effective contractions and prolonged delivery time. The objective of this study was to determine the effectiveness of lemon aromatherapy in reducing anxiety in pregnant women approaching childbirth at PMB Lismarini, Palembang. The study employed a quasi-experimental design with a one-group pretest–posttest approach and was conducted at PMB Lismarini, Palembang. The population consisted of all third-trimester pregnant women who were not allergic to essential oils. A total of 20 respondents were selected using a total sampling technique. Data analysis was performed using the Wilcoxon signed-rank test. The results showed a p-value of 0.002, indicating that lemon aromatherapy significantly reduced anxiety levels in pregnant women. It can be concluded that lemon aromatherapy has an effect on reducing anxiety in pregnant women before childbirth. Further research with a larger sample size, more rigorous study design, and comparisons with other types of aromatherapy is recommended to confirm its effectiveness.